An intelligent value stream-based approach to collaboration of food traceability cyber physical system by fog computing - Chen, Rui-Yang (Food control, 2017)
Good advanced food traceability systems help to minimize unsafe or poor quality products in food supply chain through value-based process. From the emerging technologies forthcoming for industry automation, future advanced food traceability system must consider not only cyber physical system (CPS) and fog computing but also value-added business in food supply chain. Accordingly, this study presents a novel intelligent value stream-based food traceability cyber physical system approach integrated with enterprise architectures, EPCglobal and value stream mapping method by fog computing network for traceability collaborative efficiency. Furthermore, the proposed intelligent approach explores distributive and central traceable stream mechanism in assessing the most critical traceable events for tracking and tracing process. Successful case study, software system design and implementation demonstrated the performance of the proposed approach. Furthermore, experiment shows the better results obtained after the simulation execution for intelligent predictive algorithm. •A novel intelligent value stream-based food traceability cyber physical system is created.•This paper describes a distributive and central traceable stream mechanism for traceability process.•The EA, EPCglobal and VSM methods by fog computing are used traceability efficiency.•The proposed approach aimed at optimizing complex CPS-based food traceability system in food supply chain.•This paper explores information system design architecture of intelligent CPS-based food traceability system.